The Effect of Bangerter Filters on Visual Acuity and Contrast Sensitivity With External Noise - Zhang, Pan; Wang, Hanlin; Ren, Weicong; Guo, Huanhuan; Yang, Jiayi; Tao, Jiayu; Yang, Zhijie; Li, Ying; Chen, Lijun; Zhang, Yajing; Wu, Di (Frontiers in Neuroscience, 2022)
It is critical to address the relationship between density label of Bangerter filters and expected visual acuity, and how filters modulate contrast sensitivity (CS) at different spatial frequency and external noise levels. In the current study, the monocular visual acuity and CS at ten spatial frequencies and three noise levels were measured in normal subjects wearing no filters, 0.8, 0.4, or 0.2 Bangerter filters. Compared with the baseline condition (no filter worn), Bangerter filters degraded both visual acuity and contrast sensitivity function (CSF) in zero-noise conditions, but the reduction of both visual functions did not correlate with each other at any filter level. In addition, the stronger the filter was, the worse both visual functions became. In contrast, when external noise was present, filters improved the contrast sensitivity at low frequencies but deteriorated it at intermediate and high spatial frequencies. The perceptual template model was used to reveal the corresponding mechanism accounted for filter-induced visual function changes. Although the internal process in visual system should not be affected by the filters, the measurement of parameters was biased. To be specific, (1) the internal additive noise was elevated at all frequencies; (2) the perceptual template was improved at low spatial frequencies but impaired at intermediate spatial frequencies; and (3) the changes in both factors were highly dependent on filter intensity. We conclude that Bangerter filters influence visual acuity and contrast sensitivity differently and that their effect on contrast sensitivity depends on spatial frequency and noise.